The climate impacts of healthcare digitalization: A scoping review - Nissinen, Ari; Pitkänen, Atte; Barchuk, Anton; Hosseinian, Aida; Johansson, Annika; Kaisti, Matti; Karvonen, Jaakko; Marttinen, Pekka; Moen, Hans; Peltola, Emilia; Sokka, Laura; Tikkinen, Kari A. O. (SAGE, 2026)
OBJECTIVE The rapid digitalization of healthcare has implications for its carbon footprint. The goal of this scoping review was to identify how digitalization is proceeding in healthcare and the mechanisms through which it can affect the climate impacts of healthcare.
METHODS The scoping review was conducted following PRISMA guidelines and utilized the databases Web of Science and PubMed to identify literature on the climate impacts of digitalization in healthcare. The literature search identified 32 relevant studies. In addition, diagnostics, overdiagnosis, self-tracking technologies, and artificial intelligence (AI) were identified as key topics not sufficiently represented in the literature review, and related articles were added into the material.
RESULTS Most carbon footprint analyses focused on telemedicine solutions, but research topics also included health informatics, education, diagnoses, overdiagnosis, treatments, medical appliances, robotics, and AI. Regarding telemedicine, the carbon footprint of the virtual consultations ranged between 0·005 and 3 kgCO2e, while the in-person healthcare clinic visits ranged between 0·57 and 178 kgCO2e depending on the mode of transport used, the difference in the carbon footprint being 79-99%. Although the transparency of carbon footprint analyses was often low, system boundaries were often different, and the evidence for digitalization decreasing or increasing climate impacts was limited.
CONCLUSIONS The findings highlight the need for future research on these topics and that leadership and setting strategic goals in particular were missing in the literature. Our scoping review also presents a framework for digitalization-related topics and means for advancing a lower carbon footprint in healthcare.